Comparative Proteomics at the Critical Node of Vigor Loss in Wheat Seeds Differing in Storability - Chen, Xiuling; Börner, Andreas; Xin, Xia; Nagel, Manuela; He, Juanjuan; Li, Jisheng; Li, Na; Lu, Xinxiong; Yin, Guangkun (Frontiers in Plant Science, 2021)
The critical node (CN, 85% germination) of seed viability is an important threshold for seed regeneration decisions after long-term conservation. Dependent on the germplasm, the storage period until CN is reached varies and information on the divergence of the proteomic profiles is limited. Therefore, the study aims to identify key proteins and mechanisms relevant for a long plateau phase and a late CN during artificial seed ageing of wheat. Seeds of the storage-tolerant genotype (ST) TRI 23248, and the storage-sensitive genotype (SS) TRI 10230 were exposed to artificial ageing (AA) and extracted embryos of imbibed seeds were analyzed using an iTRAQ-based proteomic technique. ST and SS required AA for 24 and 18 days to reach the CN, respectively. Fifty-seven and 165 differentially abundant proteins (DAPs) were observed in the control and aged groups, respectively. Interestingly, a higher activity in metabolic processes, protein synthesis, transcription, cell growth/division, and signal transduction were already found in imbibed embryos of control ST seeds. After AA, 132 and 64 DAPs were accumulated in imbibed embryos of both aged ST and SS seeds, respectively, which were mainly associated with cell defense, rescue, and metabolism. Moreover, 78 DAPs of ST appeared before CN and were mainly enriched in biological pathways related to the maintenance of redox and carbon homeostasis and they presented a stronger protein translation ability. In contrast, in SS, only 3 DAPs appeared before CN and were enriched only in the structural constituents of the cytoskeleton. In conclusion, a longer span of plateau phase might be obtained in seeds when proteins indicate an intense stress response before CN and include the effective maintenance of cellular homeostasis, and avoidance of excess accumulation of cytotoxic compounds. Although key proteins, inherent factors and the precise regulatory mechanisms need to be further investigated, the found proteins may also have functional potential roles during long-term seed conservation.